The determinants of gold price in Malaysia / Nurul Afiqah Rosli - Rosli, Nurul Afiqah (Faculty of Business and Management, 2017)
Gold is a precious metal which serves as both financial and real assets. The value of gold in the society goes more than just economic, as it is also treasured as a storage and display of mammon and culture. In the long-run, its prices keep increasing due to high demand and inadequate supply worldwide. However, in the short-run, its price seems to be volatile due to various potential reasons. Therefore, this study was conducted to determine the factors influencing gold prices in Malaysia. Researcher investigates the relationship of dependent variable, gold price between the independent variable inflation rate, interest rate and crude oil price. In order to achieve the objective, the researcher using multiple linear regression models to identify the significant variable and researcher use annual data from years 1996 until 2015. From the analysis, have independent variable they have a significant relationship with the gold price in Malaysia. interest rate and crude oil price have a significant relationship with gold price in Malaysia, while inflation rate do not have a significant relationship.